2002
DOI: 10.1111/j.1567-1364.2002.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of basidiomycetous yeasts: a comparison of large subunit D1/D2 and internal transcribed spacer rDNA regions

Abstract: Basidiomycetous yeasts in the Urediniomycetes and Hymenomycetes were examined by sequence analysis in two ribosomal DNA regions: the D1/D2 variable domains at the 5' end of the large subunit rRNA gene (D1/D2) and the internal transcribed spacers (ITS) 1 and 2. Four major lineages were recognized in each class: Microbotryum, Sporidiobolus, Erythrobasidium and Agaricostilbum in the Urediniomycetes; Tremellales, Trichosporonales, Filobasidiales and Cystofilobasidiales in the Hymenomycetes. Bootstrap support for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
217
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(230 citation statements)
references
References 73 publications
(110 reference statements)
9
217
1
3
Order By: Relevance
“…1) were different from those depicted in the ITS tree. Such discordances have been reported in other groups of basidiomycetous yeasts (Bai et al, 2002;Scorzetti et al, 2002). In order to confirm the phylogenetic positions of the two groups, 18S rDNA sequences of the representative strains CB 286 T and CB 346 T were determined and aligned with those of reference taxa, including all described Bensingtonia species and related urediniomycetous yeast taxa.…”
Section: Molecular Phylogenetic Analysismentioning
confidence: 72%
See 2 more Smart Citations
“…1) were different from those depicted in the ITS tree. Such discordances have been reported in other groups of basidiomycetous yeasts (Bai et al, 2002;Scorzetti et al, 2002). In order to confirm the phylogenetic positions of the two groups, 18S rDNA sequences of the representative strains CB 286 T and CB 346 T were determined and aligned with those of reference taxa, including all described Bensingtonia species and related urediniomycetous yeast taxa.…”
Section: Molecular Phylogenetic Analysismentioning
confidence: 72%
“…1), the two groups were located in the Kondoa clade, Agaricostilbum lineage of urediniomycetous yeasts (Scorzetti et al, 2002). They clustered together with Bensingtonia yuccicola and an undescribed Bensingtonia species represented by strain PYCC 5562 (Fig.…”
Section: Molecular Phylogenetic Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have claimed that conspecific yeast strains usually have fewer than 1% nucleotide differences in the ITS 1 and 2 regions overall (Nagahama et al 1999; Sugita et al 1999a, b; Scorzetti et al 2002). However, the present study showed that divergent ITS1 and ITS2 types which differed by up to 15.6% and 20.5% base mismatches, respectively, coexist in the single genome of strain CBS 215.…”
Section: Discussionmentioning
confidence: 99%
“…The rDNA ITS region is one of the most frequently used molecular markers in phylogeny and identification of yeasts at the species level (James et al 1996; Montrocher et al 1998; Sugita et al 1999a, b; Fell et al 2000; Scorzetti et al 2002; Kurtzman and Robnett 2003) and has been selected as a universal DNA barcode marker for Fungi (Schoch et al 2012). Previous studies have claimed that conspecific yeast strains usually have fewer than 1% nucleotide differences in the ITS 1 and 2 regions overall (Nagahama et al 1999; Sugita et al 1999a, b; Scorzetti et al 2002).…”
Section: Discussionmentioning
confidence: 99%